FROM THE HISTORY OF THE CATTLE BREEDING DEVELOPMENT IN POLTAVA REGION (the end of XIX – beginning of XX century) - Бондаренко, О. М. (Scientific Progress & Innovations, 2015)
Some aspects of the history of the cattle breeding development in Poltava region in the end of XIX – beginning of XX century are considered on the basis of literary sources. Two factors had special influence on the breeding of cattle: the increase of urban population and the intensification of land cultivation. The growth of commercial agriculture, which demanded the increase of work productivity, resulted, on the one hand, to more enhanced working cattle breeding than productive, and on the other, due to stratification in rural areas, growth of livestock only in the affluent part of the peasantry, which had a pulling force. For Poltava region breeding cattle at all stages of historical development was very important, providing the population with high-calorie meat and dairy products.